FOSTERING STUDENTS’ MATHEMATICAL LITERACY ABILITY THROUGH DIFFERENTIATED INSTRUCTION AND RME-APPROACH: AN ACTION RESEARCH (Proceedings of the International Conference on Education, 2025)
Indonesian students' low math literacy is evident from the stagnant PISA trends and classroom observations in a Junior High School (JHS) in Bantul, Yogyakarta. The observed low math literacy is due to a lack of innovative teaching methods that do not align with students' learning needs. Specifically, in algebra, students struggle because lessons often introduce formal elements and operations without clear explanations. This research aims to improve math literacy in this JHS through differentiated learning with the Realistic Mathematics Education (RME) approach. Using classroom action research and an embedded-RTI model, the study focused on providing teaching materials tailored to students' needs, improving their literacy skills. The study was conducted over two cycles with 32 students, with the first cycle focusing on mathematical modeling for one-variable linear equation and the second on the one-variable linear equation equivalent. Data were collected through math literacy tests and learning observation sheets to gather both quantitative and qualitative data. Quantitative data showed improvements in students' math literacy scores, while qualitative data provided insights into the effectiveness of the learning process. Results indicated that RME-based differentiated learning significantly improved students' math literacy on one-variable linear equation. Math literacy improved from 12.5% to 62.5% in first cycle and 62.5% to 78.125% in second cycle which measured by three components of mathematical literacy ability, such as formulate, employ, and evaluate. Learning implementation also improved, from 74% to 84% in the first cycle, and from 80% to 88% in the second cycle. These findings suggest that differentiated instruction using the RME approach can enhance math literacy in Indonesian JHS students. However, it should be considered that this study had several limitations such as limited subject was only in a class of a school and occurred in six meetings for the intervention. For future researchers can adapt their intervention setting with this consideration
Keywords: Algebra; Action Research; Mathematics Education; Mathematical Literacy Ability; One-variable Linear Equation; Realistic Mathematics Education